Pengaruh Menghafal Perkalian dalam Menyelesaikan Soal Matematika Terhadap Hasil Belajar Siswa Selama Program Kampus Mengajar - Zakia Uliyah Fadillah; Wahyullah Alannasir; Rahmawati Rahmawati; Andi Besse Marda; Erwin Nurdiansyah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The purpose of the researcher in this study is to find out whether there is an effect of memorizing multiplication in solving math problems in student learning outcomes in class V SD Inpres Kajenjeng during the Kampus Mengajar program in Manggala District, Makassar City. This research method uses quantitative methods. This type of research is quasi-experimental research or Quasi Experimental Design. Quasi Experimental Design or quasi-experimental research is carried out without a comparison class or control class. The type of experiment used is One Group Pretest-Posttest. This type of research was measured using a pre-test which was conducted before being given treatment and a post-test which was conducted after being given treatment. The result of this research is that there are significant differences before and after being given treatment. In student learning outcomes, students get a value of -3.529 < 2.160 based on the results of posttest data calculations using independent t-test.